Comparative Study on the Macroscopic and Microscopic Properties of UHPC Mixed with Limestone Powder and Slag Powder. (7th April 2021) - Yang, Menghui; He, Zhen; Chen, Xia; Li, Mingxia; Peng, Ziling
Abstract : This paper explores the development laws of the fluidity, compressive strength, and autogenous shrinkage of ultrahigh performance cement (UHPC) mixed with limestone powder (LP) and highly active ground slag powder (SP). A microscopic analysis was conducted on the hydration products and pore structures. Through quantitative research on the packing density and fractal dimension of particles in different systems, the relationship between particle characteristics and UHPC properties was established. As a result, the packing densities of the UHPC mixed solely with LP (binary system) and UHPC mixed with LP and silica fume (ternary system) are higher than those of UHPC mixed with the same amount of SP and the benchmark UHPC system; fractal dimension of particle size distribution is closely related to packing density. The LP-cement-silica fume ternary system was lowly hydrated, but it has a good grain composition and high density of slurry, which improved the compressive strength of UHPC. The compressive strength of UHPC mixed with 50% LP witnessed a more obvious decline than that of the ternary system and the one with the same amount of SP. The reason lies in the decrease in slurry due to a lack of sufficient active constituents, and the hydration products were far from enough to fill the pores in the system. LP can also inhibit autogenous shrinkage to the greatest degree for the LP-mixed binary system performed best in such inhibition.